Global health from home - results from a German student-led online lecture series during COVID-19. (20th October 2021) - Gepp, S; Gök, S; Jung, L; Kreitlow, A; Machleid, F; Nordmann, K; Weber, L
Abstract: Background: The COVID-19 pandemic calls for a skilled health workforce, yet global health is largely missing in the medical curriculum in Germany. The interdisciplinary national student "Global Health Network" therefore initiated an online lecture series. "Global Health - perspectives, opportunities and challenges" included 14 lectures on a range of topics held by German and international academics from October 2020 to January 2021. Methods: Evaluations were performed prior to, at midterm and after the series, including 5-point likert scales and open questions. Using quantitative and qualitative approaches, participants' motivation and learning outcomes of global health education were analysed. Results: A total of 1393 students registered for the series. Individual lectures attracted on average 400 participants, mainly female medical students between 20-25 years, but also a variety of ages, genders and disciplines. Main reasons for participation included interest in COVID-19-related developments, learning about global health-specific topics, and professional development. More than 40% of participants reported to know little about global health before attending; after the lecture series, only 10% made this statement. In addition, 90% of participants perceived an increase of motivation to learn more about the topics, while about 40% gained motivation to become practically involved in the field. The lecture series was accredited in the curriculum at some universities, thus innovating the curriculum and enabling formal credits. Conclusions: The new model of student-led online teaching proved to be feasible and demonstrated students' interest and positive impact on global health knowledge. Further institutional change and inclusion of global health in the curricula have to follow. Key messages: Students need global health education to respond to global health-related challenges. Volunteer student-led initiatives can increase knowledge and interest and be an important driver for change towards improving global health education.